Power Market Structure: Revisiting Policy Options - Vagliasindi, Maria (World Bank, 2015)
The current distribution of power markets around intermediate structures between full integration and unbundling suggests that there has not been a linear path to reform in practice. Instead, many developing countries may retain intermediate structures in the foreseeable future. This possibility exposes a large gap in understanding about power market structures, since most theoretical work has focused on the two extreme structures and there is limited evidence on the impact of unbundling for developing countries.